Extraction-Chromogenic System for Nickel(II) Based on 5-methyl-4-(2-thiazolylazo)resorcinol and Aliquat 336 - Galya Konstantinova Toncheva; Danail Georgiev Hristov; Nikolina Petkova Milcheva; Kiril Blazhev Gavazov (Acta Chimica Slovenica, 2020)
A water-isobutanol extraction-chromogenic system for NiII, based on the azo dye 5-methyl-4-(2-thiazolylazo)resorcinol (MTAR; H2L) and the ionic liquid Aliquat 336 (A336), was studied. Under the optimal conditions (cMTAR = 2.0 × 10–4 mol dm–3, cA336 = 5.6 × 10–3 mol dm–3, pH 8.5 and extraction time t = 1 min), NiII is extracted as a ternary complex which can be represented by the formula (A336+)2[Ni(L2-)2]. In the absence of A336, or in a slightly acidic medium, a binary complex, [Ni(HL-)2], with an absorption maximum at l = 548 nm and a shoulder at 590 nm is formed. The following extraction-spectrophotometric characteristics were determined at the above-mentioned optimal conditions: lmax (545 nm), molar absorptivity (5.0 × 104 dm3 mol–1 cm–1), Sandell’s sensitivity (1.2 × 10–3 μg cm–2), Beer’s law limits (0.05–3.1 mg cm–3), constant of extraction (Log K = 6.1) and fraction extracted (99.2%). The effect of foreign ions was studied; the most serious interferences were caused by CoII, CuII and CrIII.